Can Top-Down Controls Expand the Ecological Niche of Marine N2 Fixers? - Landolfi, Angela; Prowe, A. E. Friederike; Pahlow, Markus; Somes, Christopher J.; Chien, Chia-Te; Schartau, Markus; Koeve, Wolfgang; Oschlies, Andreas (Frontiers in Microbiology, 2021)
The ability of marine diazotrophs to fix dinitrogen gas (N₂) is one of the most influential yet enigmatic processes in the ocean. With their activity diazotrophs support biological production by fixing about 100-200 Tg N/yr of bioavailable nitrogen (N), an essential limiting nutrient. Despite their important role, the factors that control the distribution of diazotrophs and their ability to fix N₂ are not fully elucidated. We discuss insights that can be gained from the emerging picture of a wide geographical distribution of marine diazotrophs and provide a critical assessment of environmental (bottom-up) versus trophic (top-down) controls. We present a simplified theoretical framework to understand how top-down control affects competition for resources that determine ecological niches. Selective grazing on non-fixing phytoplankton is identified as a critical process that can broaden the ability of diazotrophs to compete for resources in top-down controlled systems and explain an expanded ecological niche for diazotrophy. Our simplified analysis predicts a larger importance of top-down control in nutrient-rich systems where grazing controls the faster growing phytoplankton, allowing the slower growing diazotrophs to become established. However, these predictions require corroboration by experimental and field data, together with the identification of specific traits of organisms and associated trade-offs related to selective top-down control. Elucidation of these factors could greatly improve our predictive capability for marine N2 fixation. The susceptibility of this key biogeochemical process to future changes may not only be determined by changes in environmental conditions but also via changes in the ecological interactions.